Trace metals in aquatic systems - Mason, Robert P. (Robert Peter), 1956- (Hoboken, NJ : John Wiley & Sons, 2013)
"The textbooks that currently exist do not deal with this particular subject in a comprehensive fashion, and therefore this book is being proposed to full this gap"--
3.4.3 Dissolved-particulate partition coefficients3.4.4 Adsorption isotherms; 3.4.5 A complexation-based model for adsorption; 3.5 Redox transformations and thermodynamic calculations; 3.5.1 Electrochemistry and the equilibrium constant; 3.5.2 The range in electrode potential and the stability of water; 3.5.3 Equilibrium calculations involving redox reactions; 3.5.4 Environmental considerations and controlling reactions; 3.6 Chapter summary; References; Problems; CHAPTER 4: Modeling approaches to estimating speciation and interactions in aqueous systems; 4.1 Introduction.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Trace elements -- Analysis; Water -- Analysis; Water chemistry; SCIENCE -- Chemistry -- Organic; Trace elements -- Analysis; Water -- Analysis; Water chemistry; Electronic books; Electronic books